2020
DOI: 10.7554/elife.55365
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between integration and non-integration strategies in perceptual decision making

Abstract: Many tasks used to study decision-making encourage subjects to integrate evidence over time. Such tasks are useful to understand how the brain operates on multiple samples of information over prolonged timescales, but only if subjects actually integrate evidence to form their decisions. We explored the behavioral observations that corroborate evidence-integration in a number of task-designs. Several commonly accepted signs of integration were also predicted by non-integration strategies. Furthermore, an integr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 63 publications
8
91
1
Order By: Relevance
“…Recent work has suggested that when traditional evidence accumulation tasks are performed, it is hard to dissociate whether subjects are combining information across samples, or whether conventional analyses may be disguising a simpler heuristic ( Waskom and Kiani, 2018 ; Stine et al, 2020 ). In particular, an alternative decision-making strategy which does not involve temporal accumulation of evidence is to detect the single most extreme sample.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has suggested that when traditional evidence accumulation tasks are performed, it is hard to dissociate whether subjects are combining information across samples, or whether conventional analyses may be disguising a simpler heuristic ( Waskom and Kiani, 2018 ; Stine et al, 2020 ). In particular, an alternative decision-making strategy which does not involve temporal accumulation of evidence is to detect the single most extreme sample.…”
Section: Resultsmentioning
confidence: 99%
“…The number and location of the different directional cues within the song was systematically varied (Fig. S1), which was critical for calibrating the model parameters (Stine et al, 2020). For instance, responses to songs with serially conflicting directional information in which syllables at the beginning of the song indicated a female in the direction of one speaker and those at the end of the song indicated a female in the opposite direction reveal over how many syllables males integrate and when decisions are fixed.…”
Section: Resultsmentioning
confidence: 99%
“…The LDDM builds off the simplest form of a drift-diffusion model, and various extensions and related models have been proposed to better fit behavioral data, including urgency signals [47,[59][60][61][62], history-dependent effects [63][64][65][66][67][68][69], imperfect sensory integration [35], confidence [58,70,71], and multi-alternative choices [72,73]. More broadly, it remains unclear whether the drift-diffusion framework in fact underlies perceptual decision making, with a variety of other proposals providing differing accounts [38,74,75]. We speculate that the qualitative learning speed/instantaneous reward rate trade-off that we formally derive in the LDDM would also arise in other models of within-trial decision making dynamics.…”
Section: Discussionmentioning
confidence: 99%